2020
DOI: 10.1007/s10643-020-01117-6
|View full text |Cite
|
Sign up to set email alerts
|

“Everybody has to get a Chance to Learn”: Democratic Aspects of Digitalisation in Preschool

Abstract: The aim of this article is to examine the ways in which curriculum goals on digitalisation are viewed in relation to the overarching democratic mission of Swedish preschools. Groups of preschool staff from three preschools located in different areas were interviewed with the focus on how they discuss democracy and the democratic aspects of digital tools and children’s digital competence, which are concepts used in the curriculum. Collective mind maps – constructed by the participants – were used as focal point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…In contrast, it has also been shown that some PSTs are not interested in digital tools and opportunities they provide (Enochsson and Ribaeus, 2021); Kjällander and Johnson Frankenberg (2018). Whether PSTs find digital tools useful has been linked to their views of children and democracy (Enochsson and Ribaeus, 2021). Another reason for reluctance is PSTs' concerns that digital technology is socially and physically limiting (Palaiologou 2016).…”
Section: Digital Tools In Preschoolsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, it has also been shown that some PSTs are not interested in digital tools and opportunities they provide (Enochsson and Ribaeus, 2021); Kjällander and Johnson Frankenberg (2018). Whether PSTs find digital tools useful has been linked to their views of children and democracy (Enochsson and Ribaeus, 2021). Another reason for reluctance is PSTs' concerns that digital technology is socially and physically limiting (Palaiologou 2016).…”
Section: Digital Tools In Preschoolsmentioning
confidence: 99%
“…Thus, PSTs themselves need to decide when, how, and why digital tools should be used. When teachers at different preschools do not have similar competence and/or views on digital tools, children have to develop their digital competence under very different conditions (Enochsson and Ribaeus, 2021). Even though the use of tablets has been increasing in Swedish preschools for some time now (Fridberg, Thulin, and Redfors 2018;Marklund and Dunkels 2016), many preschools still only have access to one or two tablets per department (Otterborn, Schönborn, and Hultén 2019).…”
Section: The Swedish Contextmentioning
confidence: 99%
“…The role of the pedagogue in relation to the children is an important factor for meaning-making with tablets (Kjällander, 2011). Pedagogues need different types of scaffolding, and their views of children and cultural interplay are important starting-points (Marsh et al, 2016;Enochsson & Ribeaus, 2020).…”
Section: Digital Literacymentioning
confidence: 99%
“…Work in preschool education requires simultaneous professional and personal development since interaction with preschool children is based on the teacher's creativity and improvisation. In wartime, the training of a future specialist relates to the mastery of modern technologies and teaching tools, finding and implementing new forms of work with children (Enochsson & Ribaeus, 2021).…”
Section: Introductionmentioning
confidence: 99%